Occupational health: does compliance with physical activity recommendations have a preventive effect on musculoskeletal symptoms in computer workers? - Moreira, Sara (2021)
A lack of physical activity in computer workers (CW) can contribute to the development of musculoskeletal symptoms (MSS). Aim: (i) Evaluate MSS over a 12 month and 7 days period, (ii) determine physical activity (PA) levels and compliance with World Health Organization (WHO) PA recommendations, and (iii) assess the relationship between compliance with WHO PA recommendations and MSS. A cross-sectional observational study comprising 119 computer workers. The Nordic Musculoskeletal Questionnaire (NMQ) was used to evaluate the MSS and the International Physical Activity Questionnaire (IPAQ) was used to analyse the perception of the level of PA. MSS occurred in the lumbar region (56.3%), neck (43.7%), and shoulders (39.5%). 44.7% of the participants reported a low level of PA. The percentage of compliance was similar among women and men (62.2% vs. 58.5%, respectively). Negative correlations were found between pain intensity and metabolic equivalent values. The participants who followed the WHO PA recommendations reported a lower frequency of MSS compared to those who did not, but the differences were not statistically significant. It was possible to conclude that computer workers presented a higher frequency of MSS in the lower back, neck, and shoulders. Regarding the level of PA, participants were mostly classified as low. Participants who followed the WHO PA recommendations reported lower MSS than those who did not. This finding could be important in obtaining successful programs that promote health-oriented physical activity in this group of workers.